Odpowiedź :
Odpowiedź:
1. (-3) + (-6)= (-9)
(-8) + (-5)= (-13)
(-12) + (-4)= (-16)
(-9) + (-9)= (-18)
(-4) + (-10)= (-14)
(-10) + (-15)= (-25)
2.
4 + (-9)= (-5)
8 + (-12)= (-4)
15 +(-6)= 9
11 + (-11)= 0
(-2) + 3= 1
(-6) + 9= 3
(-8) + 7= (-1)
(-10) + 6= (-4)
(-14) + 14= 0
szczegółowe wyjaśnienie:
mam nadzieję, że pomogłam
Odpowiedź:
Szczegółowe wyjaśnienie:
Odpowiedź:
1. (-3) + (-6)= (-9)
(-8) + (-5)= (-13)
(-12) + (-4)= (-16)
(-9) + (-9)= (-18)
(-4) + (-10)= (-14)
(-10) + (-15)= (-25)
2.
4 + (-9)= (-5)
8 + (-12)= (-4)
15 +(-6)= 9
11 + (-11)= 0
(-2) + 3= 1
(-6) + 9= 3
(-8) + 7= (-1)
(-10) + 6= (-4)
(-14) + 14= 0
Wyjaśnienie: Powinno byc dobrze